(untitled) (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
Author Mr. Vijaya Kumar Voleti Assistant Professor, School of Pharmacy, Sathyabama Institute of Science and Technology, Chennai, Tamil Nadu, India Abstract: Quality Control (QC) and Quality Assurance (QA) are integral components of pharmaceutical manufacturing, ensuring the consistency, safety, and efficacy of drug products. This section explores the principles and practices of QC and QA in the pharmaceutical industry. The distinction between QC and QA is clarified, with QC focusing on product testing and QA encompassing broader quality management systems. Various aspects of quality control are examined, including raw material testing, in-process controls, and finished product analysis. Analytical techniques commonly used in pharmaceutical QC, such as chromatography, spectroscopy, and dissolution testing, are discussed. The concept of specifications and their development is explored, highlighting the importance of setting appropriate acceptance criteria. Quality assurance principles, including risk management, change control, and continuous improvement, are addressed. The role of documentation in quality systems, including standard operating procedures (SOPs) and batch records, is emphasized. Good Laboratory Practices (GLP) and their application in quality control laboratories are discussed. The importance of method validation and analytical instrument qualification in ensuring reliable test results is highlighted. Quality metrics and their use in monitoring and improving manufacturing processes are explored. Keywords: Product testing, Specifications, Method validation, Risk management, Compliance, Continuous improvement View PDF